Scoping review and interpretation of myofascial pain/fibromyalgia syndrome: An attempt to assemble a medical puzzle. - Shiloh Plaut (PLoS ONE)
Background Myofascial Pain Syndrome (MPS) is a common, overlooked, and underdiagnosed condition and has significant burden. MPS is often dismissed by clinicians while patients remain in pain for years. MPS can evolve into fibromyalgia, however, effective treatments for both are lacking due to absence of a clear mechanism. Many studies focus on central sensitization. Therefore, the purpose of this scoping review is to systematically search cross-disciplinary empirical studies of MPS, focusing on mechanical aspects, and suggest an organic mechanism explaining how it might evolve into fibromyalgia. Hopefully, it will advance our understanding of this disease. Methods Systematically searched multiple phrases in MEDLINE, EMBASE, COCHRANE, PEDro, and medRxiv, majority with no time limit. Inclusion/exclusion based on title and abstract, then full text inspection. Additional literature added on relevant side topics. Review follows PRISMA-ScR guidelines. PROSPERO yet to adapt registration for scoping reviews. Findings 799 records included. Fascia can adapt to various states by reversibly changing biomechanical and physical properties. Trigger points, tension, and pain are a hallmark of MPS. Myofibroblasts play a role in sustained myofascial tension. Tension can propagate in fascia, possibly supporting a tensegrity framework. Movement and mechanical interventions treat and prevent MPS, while living sedentarily predisposes to MPS and recurrence. Conclusions MPS can be seen as a pathological state of imbalance in a natural process; manifesting from the inherent properties of the fascia, triggered by a disrupted biomechanical interplay. MPS might evolve into fibromyalgia through deranged myofibroblasts in connective tissue ("fascial armoring"). Movement is an underemployed requisite in modern lifestyle. Lifestyle is linked to pain and suffering. The mechanism of needling is suggested to be more mechanical than currently thought. A "global percutaneous needle fasciotomy" that respects tensegrity principles may treat MPS/fibromyalgia more effectively. "Functional-somatic syndromes" can be seen as one entity (myofibroblast-generated-tensegrity-tension), sharing a common rheuma-psycho-neurological mechanism.